Workplace abuse among correctional health professional in New South Wales, Australia - Cashmore, A.; Indig, D.; Hampton, S.; Hegney, Desley; Jalaludin, B. (CSIRO Publishing, 2012)
Objective: Studies have found that health workers are at elevated risk of being abused while at work. Little is known, however, about workplace abuse among correctional health professionals. We implemented a cross-sectional study to investigate the prevalence, sources and consequences of workplace abuse among correctional health professionals in New South Wales, Australia. Methods. All employees of Justice Health (a statutory health corporation) were invited to complete a self-administered survey, which was delivered via the internet. Among nurses, medical doctors and allied health professionals, 299 usable surveys were returned; a response rate of 42%. Results: In the preceding 3 months, 76% of participants had personally experienced some form of abuse in their workplace, all but one of whom recalled verbal abuse. Only 16% reported physical abuse. Seventy per cent reported feeling safe in their workplace. Patients were identified as the main perpetrators of abuse, followed by fellow health staff. Participants felt that incidents of workplace abuse increased their potential to make errors while providing care to patients and reduced their productivity while at work. Conclusions: Compared with health workers who practise in a community setting, the risk of physical abuse among correctional health professionals appears to be low.